Forging an interdisciplinary lens for understanding community digital archives of South Asian diaspora - Parmar, Sharika (Frontiers in Sociology, 2025)
Different communities have begun archiving their own experiences and histories as a way to reclaim narratives and contend with their own identities and belonging. As the types of archives diversify and the role of digital technologies in archival practices expands, we are increasingly seeing digital community archival efforts. While archives have been key for carrying out research in the social sciences and the humanities, and are periodically found as topics of study in disciplinary subfields concerning themselves with the digital, there is little research on the specific subject of community digital archives. In this essay, I argue that community digital archives are important objects of sociological and historical inquiry. I discuss two community digital archives of the South Asian diaspora – the South Asian American Digital Archive (SAADA) and 1947 Partition Archive. I show that they offer insights into migration histories and notions of belonging and identity of South Asian diaspora not only through the digital records they produce, but also through how they operate using digital connectivity. I demonstrate that an interdisciplinary lens is key for critically engaging with these archives.